Alternative cGAS signaling promotes herpes simplex encephalitis - Liraz Shmuel-Galia; Zhaozhao Jiang; Laurel Stine; Sara Cahill; Sze-Ling Ng; Ruth Wilson; Richard Kumaran Kandasamy; Evelyn A. Kurt-Jones; Joshi M. Ramanjulu; John Bertin; Viera Kasparcova; G. Scott Pesiridis; et al. (Proceedings of the National Academy of Sciences, 2025)
During infection, foreign DNA is sensed by cyclic GMP-AMP synthase (cGAS) leading to the production of cGAMP, STING-dependent type I interferon and proinflammatory cytokine expression, and autophagy. To prevent a response to self-DNA, cGAS activity is tightly regulated. Dysregulation of cGAS underpins interferonopathies, such as Aicardi–Goutières syndrome, as well as Lupus and neurodegenerative diseases like Parkinson’s disease. Thus, cGAS and its product cGAMP are therapeutic targets. However, if cGAS functions independently of cGAMP signaling is undefined. Here, we identified an alternative signaling pathway that cGAS engages independent of cGAMP synthesis. We demonstrate that alternative cGAS signaling promotes hyperexpression of CXCL1 and enhanced neutrophil recruitment that facilitates viral dissemination during herpes simplex encephalitis. Our study reports of an alternative cGAS response independent of cGAMP, highlighting a previously uncharacterized scaffold function for cGAS.